Disruption in the consumer decision-making? Critical analysis of the consumer’s decision making and its possible change by the COVID-19 - et. al., Ríos Lama Cristian Armando, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A multidisciplinary concept of consumer science and a disruptive pandemic. How are these elements intertwined? In this sense the purpose of this article is to know how the purchase decision could be changed by the covid-19. A holistic analysis of both the psychological and economic effects of a pandemic, impacts from the generational theory, and how this could cause security to become more relevant was carried out. It was carried out a systematic review of scientific literature consulting 304 articles, being 106 the selected ones, under high impact criteria. It is presumed that consumers will make slightly more rational decisions, although this will be subject to factors inherent to specific scenarios, so it is necessary to perform multivariate empirical research